Cyber (In)security of Personal Data and Information in Times of Digitization - Dvojmoč, Miha; Tancer Verboten, Mojca (Medicine, Law & Society, 2022)
In an employment relationship, work and pay are no longer the only important aspects, as importance is increasingly shifting toward obligations concerning the protection of personal data and privacy arising from the prohibition of causing harm to the employer and the duty of loyalty to the employer. The article deals with the constitutionally protected right to privacy and the protection of personal data from the point of view of ensuring cyber security at the employer. The employer is obligated to protect the right to privacy by legal provisions, whereas from the point of view of ensuring the protection of privacy and information, the employer must protect, first and foremost, the personal data of employees. The main purpose of the legal protection of personal data is the lawful and fair processing of the personal data of individuals. Employers are thus facing an increasing number of risks related to the safety of employees and the security of business processes, and it is therefore important to establish comprehensive corporate security to ensure adequate security across all levels.